1981
DOI: 10.1159/000158357
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Morphological Properties of Human Omental Resistance Vessels

Abstract: We have examined the functional and morphological properties of arterial resistance vessels with lumen diameters about 200 µm from the human omentum. The vascular smooth muscle cells were circumferentially oriented and arranged in about 3 layers within the media. The cells, when held at a length where their contractile response was maximal, were 97 µm long and had a mean diameter of 3.9 µm. In response to maximum potassium stimulation the force developed per cell was 2.4 µN. The maximum response to norepinephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…To our knowledge, there are no corresponding studies in human mesenteric arteries. Although, a study in human omental arteries supports a normalization ratio of 0.9 (Aalkjaer and Mulvany ).…”
Section: Discussionmentioning
confidence: 98%
“…To our knowledge, there are no corresponding studies in human mesenteric arteries. Although, a study in human omental arteries supports a normalization ratio of 0.9 (Aalkjaer and Mulvany ).…”
Section: Discussionmentioning
confidence: 98%
“…In previous studies on the effect of noradrenaline in small resistance arteries (also approximately 200 pm in diameter), Aalkjzr et al found pD2 values of 6.43 in human omental arteries and 6.55 in subcutaneous vessels (1,2), and Nyborg and Mikkelsen found a pD2 of 5.96 in rat mesenteric arteries (27). Our finding of a pD, of 6.95 in bone thus suggests that bone arteries are quite sensitive to noradrenaline.…”
Section: Smooth-muscle Functionmentioning
confidence: 97%
“…Each vessel was then set to the normalized internal diameter, L " l 0.9iL "!! \π, at which contraction is thought to be optimal [26].…”
Section: Experimental Protocolmentioning
confidence: 99%